2019
DOI: 10.1016/j.jsurg.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Value of Dedicated Research Time for IMGs in Obtaining Surgical Residency Training Positions: A 10-Year Review of Applicants from a Medical College in Pakistan

Abstract: Our quasi-experimental study demonstrated a higher success rate for Aga Khan University, Medical College applicants with significant research background in the US, compared to those who did not. Better social integration, enhanced mentorship available during research, overcoming of cultural and linguistic barriers and a perception as better qualified candidate can be some factors contributing to higher success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This consistency indicates that there is a shared understanding of the necessity of regular feedback in surgical training, regardless of the role of the respondent, and that both parties understand that feedback is an integral part of each surgical procedure, reflecting a commitment to trainee development. The perceived significant value of feedback is supported by prior studies citing that residents lay emphasis on the necessity for persistent implementation of feedback [ 1 ] and that PDs indicate program success is supported by feedback that is frequent and actionable [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consistency indicates that there is a shared understanding of the necessity of regular feedback in surgical training, regardless of the role of the respondent, and that both parties understand that feedback is an integral part of each surgical procedure, reflecting a commitment to trainee development. The perceived significant value of feedback is supported by prior studies citing that residents lay emphasis on the necessity for persistent implementation of feedback [ 1 ] and that PDs indicate program success is supported by feedback that is frequent and actionable [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of feedback has been shown to limit improvement as repetition of a procedure alone cannot assure development of skills. In previous studies, residents often reported a need for improved feedback, implying the delivery method of feedback is flawed or perceptions of feedback differ between program faculty and trainees [ 2 ]. It is important to explore the different types of feedback mechanisms and their individual benefits, barriers to feedback, and discrepancies between trainees and teachers on perceptions of feedback.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well‐known that the path to entering U.S. residency is incredibly challenging for IMGs [12–14]. Given that a demonstrated involvement and interest in research is a consideration used by thoracic surgery program directors [15], there may be secondary benefits to completing a RF in the U.S. in that IMGs can strengthen their residency and fellowship applications [16, 17]. Indeed, about 80% of IMGs who completed a RF in our study pursued this training in the U.S. compared to about 5% of IMGs with a PhD earning this degree in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…These programs can benefit students looking to strengthen their application because of lower than average boards scores, to stand out among the most qualified applicants to match into a top-tier residency program, or for international medical graduates who desire to match into a United States orthopaedic residency. 11 , 12 These fellowships have shown value in other specialties. Mehta et al showed that plastic surgery applicants who completed a research fellowship program were significantly more likely to match into an integrated plastic surgery residency than those who did not complete a fellowship (97% vs. 81%, P < 0.05).…”
mentioning
confidence: 99%